ANALISIS PRODUKTIVITAS PROSES SPRAY PAINTING PT. RACER TECHNOLOGY BATAM - Panjaitan, Doand Geri; Anggia Arista (Computer Science and Industrial Engineering, 2024)
PT Racer Technology Batam is a private manufacturing company. This research analyzes the productivity of the work process in the spray painting department. The study aims to identify factors influencing productivity in the Spray Painting Department, understand the form of production process productivity in the Spray Painting Department, and propose improvements to enhance productivity in the production process of the Spray Painting Department. Secondary data, obtained from the productivity data of the spray painting department at PT. Racer Technology Batam, is used in this study. The data is then analyzed using the Objective Matrix (OMAX) method. The research results indicate fluctuating productivity indices each month in the spray painting department. Based on the weight calculation for each indicator, indicator A has a weight of 56%, indicator B 22%, indicator C 16%, and indicator D 7%. The productivity index calculation from January 2023 to October 2023 reveals the highest productivity index in April 2023 with a productivity value of 868 and a productivity index increase of 139.78% compared to the previous month. The highest productivity decrease occurred in August 2023 with a productivity value of 189 and a productivity index decrease of -76.14% compared to the previous month.